1989
DOI: 10.1159/000210802
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B<sub>4</sub> Receptors on Neutrophils in Patients with Psoriasis and Atopic Eczema

Abstract: Polymorphonuclear leukocyte (PMNL) infiltration is an important characteristic in psoriatic lesions. Elevated concentrations of the chemoattractant eicosanoid leukotriene B4 (LTB4) are present in psoriatic skin. Its chemotactic activity is mediated via high affinity receptors on PMNL. The goal of our work was to ascertain whether PMNL infiltration in psoriasis can be accounted for by functional abnormalities of the circulating PMNL due to alterations in the LTB4 receptor densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The normal affinity of the receptor in psoriasis argues against a genetic defect in protein structure. The defect in psoriasis seems to be specific for IZHETE binding, since our previous studies in psoriatic granulocytes showed normal binding of the arachidonic acid metabolite leukotriene Bq [26].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The normal affinity of the receptor in psoriasis argues against a genetic defect in protein structure. The defect in psoriasis seems to be specific for IZHETE binding, since our previous studies in psoriatic granulocytes showed normal binding of the arachidonic acid metabolite leukotriene Bq [26].…”
Section: Discussionmentioning
confidence: 83%
“…The defect in psoriasis seems to be specific for IZHETE binding, since our previous studies in psoriatic granulocytes showed normal binding of the arachidonic acid metabolite leukotriene Bq [26]. The reduced number of 12(S)-HETE receptors has a functional consequence in a parallel decrease of internalization of the ligand in psoriatic versus normal keratinocytes.…”
Section: Discussionmentioning
confidence: 84%
“…Neutrophils have been implicated in the pathogenesis of many diseases, including severe asthma 12, psoriasis 34, and a variety of collagen-vascular diseases 56. These cells are known to be less sensitive to glucocorticoids than other white blood cell types 7.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils have been implicated in the pathogenesis of many diseases including COPD, severe asthma, psoriasis, and a variety of collagen-vascular diseases [105,106]. These cells are less sensitive to glucocorticoids than other white blood cell types.…”
Section: Neutrophilic Inflammationmentioning
confidence: 99%